Virtual screening and molecular docking of structures with potential inhibitor of the ebolavirus glycoprotein (Research, Society and Development, 2022)
Ebola is a disease caused by viruses of the ebolavirus genus that cause hemorrhagic fever with high human mortality. Symptoms of the infection include fever, headache, joint pain, diarrhea, vomiting and stomach pain. Unfortunately, there is still no effective treatment for this disease. This work aimed to perform a virtual screening of candidates with EBOV GP inhibition potential based on pharmacophores of 4 structures from the literature. The selected candidates underwent ADME analysis and later calculations of HOMO, LUMO and electrostatic potential map. 50 structures were obtained and after selection based on their ADME characteristics only 4 candidates were chosen. In the molecular anchoring process, the structure that presented the best binding energy was ZINC12 with -4.44 kcal.mol-1 and enzyme inhibition constant Ki equal to 555.9 µM. This result is fundamental, as it will subsidize other researches such as in vitro studies, or even application in real samples.